2012
DOI: 10.1029/2011ja017073
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric scintillation over Antarctica during the storm of 5–6 April 2010

Abstract: [1] On 5 April 2010 a coronal mass ejection produced a traveling solar wind shock front that impacted the Earth's magnetosphere, producing the largest geomagnetic storm of 2010. The storm resulted in a prolonged period of phase scintillation on Global Positioning System signals in Antarctica. The scintillation began in the deep polar cap at South Pole just over 40 min after the shock front impact was recorded by a satellite at the first Lagrangian orbit position. Scintillation activity continued there for many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“…The method is an adaptation of the MIDAS (Multi-Instrument Data Assimilation System) method developed by Spencer and Mitchell (2007) and the IDA4D (Ionospheric Data Assimilation Four-Dimensional) technique by Bust et al (2004). The ionospheric electron density was reconstructed on a three-dimensional grid of resolution 4 • in latitude, 4 • in longitude and 40 km in altitude (Kinrade et al, 2011). Electron density images were produced with 10-min GPS data samples using a tomographic space-time inversion.…”
Section: Instruments and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is an adaptation of the MIDAS (Multi-Instrument Data Assimilation System) method developed by Spencer and Mitchell (2007) and the IDA4D (Ionospheric Data Assimilation Four-Dimensional) technique by Bust et al (2004). The ionospheric electron density was reconstructed on a three-dimensional grid of resolution 4 • in latitude, 4 • in longitude and 40 km in altitude (Kinrade et al, 2011). Electron density images were produced with 10-min GPS data samples using a tomographic space-time inversion.…”
Section: Instruments and Techniquesmentioning
confidence: 99%
“…6b). (Kinrade et al, 2011). For the Arctic TEC maps, a total of 57 sites were used to reconstruct TEC maps.…”
Section: Interhemispheric Asymmetry In Phase Scintillation Occurrencementioning
confidence: 99%
“…This is accomplished through the precipitation of energetic particles along magnetic field lines into the atmosphere producing the aurora, and through an intensification of electrical current flowing in the highly conducting ionospheric auroral electrojet. GPS scintillations are often observed during geomagnetically disturbed times (Prikryl et al, 2011;Kinrade et al, 2012). Investigating interhemispheric comparisons of bipolar GPS scintillation maps, Prikryl et al (2013) have reported that the scintillation occurrence is significantly higher in the southern cusp and polar cap compared to the northern regions.…”
Section: Data Handlingmentioning
confidence: 99%
“…The magnetic coupling between the interplanetary magnetic field (IMF) and the magnetosphere controls the plasma structuring [Hunsucker and Hargreaves, 2003]. Observations of scintillation at auroral and polar latitudes and the influence of the IMF on the formation and dynamics of plasma patches have been reported [Mitchell et al, 2005;De Franceschi et al, 2008;Meggs et al, 2008;Prikryl et al, 2011;Kinrade et al, 2012, and was investigated by Alfonsi et al [2011]. Their study revealed that the IMF orientation influences mainly the scintillation distribution in the magnetic local time, thus highlighting the important role of the plasma inflow and outflow from and to the magnetosphere in the noon and midnight hours.…”
Section: Introductionmentioning
confidence: 99%